2020
DOI: 10.1101/gr.261545.120
|View full text |Cite
|
Sign up to set email alerts
|

Simple and efficient profiling of transcription initiation and transcript levels with STRIPE-seq

Abstract: Accurate mapping of transcription start sites (TSSs) is key for understanding transcriptional regulation. However, current protocols for genome-wide TSS profiling are laborious and/or expensive. We present Survey of TRanscription Initiation at Promoter Elements with high-throughput sequencing (STRIPE-seq), a simple, rapid, and cost-effective protocol for sequencing capped RNA 5′ ends from as little as 50 ng total RNA. Including depletion of uncapped RNA and reaction cleanups, a STRIPE-seq library can be constr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 80 publications
2
40
0
Order By: Relevance
“…TSRT was later adapted to mapping of TSSs at single-cell resolution in methods such as C1-CAGE ( Kouno et al, 2019 ), Tn5Prime ( Cole et al, 2018 ), and low-input Parallel Analysis of RNA Ends (nanoPARE) ( Schon et al, 2018 ). Finally, Survey of TRanscription Initiation and Promoter Elements with high-throughput sequencing (STRIPE-seq) ( Policastro et al, 2020 ) removed the need for semi-suppressive PCR or tagmentation for modest RNA input amounts, and further reduced the prevalence of artifactual reads through improved oligo design and methodological optimizations.…”
Section: Molecular Approaches To Global Tss Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…TSRT was later adapted to mapping of TSSs at single-cell resolution in methods such as C1-CAGE ( Kouno et al, 2019 ), Tn5Prime ( Cole et al, 2018 ), and low-input Parallel Analysis of RNA Ends (nanoPARE) ( Schon et al, 2018 ). Finally, Survey of TRanscription Initiation and Promoter Elements with high-throughput sequencing (STRIPE-seq) ( Policastro et al, 2020 ) removed the need for semi-suppressive PCR or tagmentation for modest RNA input amounts, and further reduced the prevalence of artifactual reads through improved oligo design and methodological optimizations.…”
Section: Molecular Approaches To Global Tss Mappingmentioning
confidence: 99%
“…We therefore suggest selecting a threshold within the inflection point of the promoter proximal fraction curve to balance removal of likely artifacts with retention of weak true TSSs. We found that, in STRIPE-seq data from yeast and human cells, a threshold of three raw counts per TSS is a suitable threshold for TSS retention ( Policastro et al, 2020 ).…”
Section: Software and Analytical Considerationsmentioning
confidence: 99%
“…We recently introduced a new TSS mapping method termed Survey of TRanscription Initiation at Promoter Elements with high-throughput sequencing (STRIPE-seq) (14), a rapid, efficient, simple, and cost-effective TSS profiling approach compatible with limited input amounts. In parallel, we developed software to streamline analysis of STRIPE-seq data, as well as data resulting from other popular methods.…”
Section: Introductionmentioning
confidence: 99%
“…1a). To enrich for RNA populations of interests, these assays implement various experimental strategies, including nuclei/chromatin isolation [8][9][10][11]18 , nuclear run-on [8][9][10] or metabolic labeling 19,20 with biotin or bromo-tagged nucleotides and affinity purification, Pol II immunoprecipitation 18 , size selection 15,16 , and enzymatic elimination of non-capped RNAs [8][9][10]16 , or chemical tagging of capped RNAs [12][13][14] . We summarized key experimental steps of both 5′ and 3′ assays in Fig.…”
mentioning
confidence: 99%
“…1a). We named the 8 assays (GRO 9 /PRO-cap 10 , CoPRO 8 , Start-seq 11 , CAGE 12 , RAMPAGE 13 , NET-CAGE 14 , csRNA-seq 15 , and STRIPE-seq 16 ) from the former category as 5’ assays, because these assays enrich for active 5’ TSSs of promoters and enhancers (Fig. 1a).…”
mentioning
confidence: 99%